'Uniformity' or 'Dispersion'?—The evolution of Chinese poetic word categories' distribution patterns. (12th January 2021) - Pan, Xiaxing; Liu, Haitao
Abstract: The daily language in mainland China has experienced a shift from traditional Chinese language to modern mandarin Chinese at the beginning of the twentieth century. The Chinese poetry 'revolution'started in the 1910s is considered as a turning point in the Chinese poetry evolution process due to the novel applications of the modern Chinese language. Many temporal poetic studies consider the poems written in traditional Chinese and modern Chinese as two different genres. The two genres are saliently different in rhyme, meter, theme, etc. We aim to detect the specific properties of the evolution process of Chinese poetry in terms of the word categories' distribution patterns. For the purpose, a corpus with 438 randomly selected traditional and modern Chinese poems is built, and some quantitative language indicators (entropy, relative entropy, repeat rate) and some exploratory statistical analysis techniques applicable in corpus linguistics and quantitative linguistics (one-way ANOVA test, cluster analysis) 1 are used to abstract and analyze language data from the corpus. It is concluded that the word categories are distributed significantly differently in traditional poetry and modern poetry. The sound reasons would be that (1) traditional Chinese poetry is more likely to focus on the application of some specific content word categories, for example, nouns, but not auxiliary words and (2) modern poems tend to choose more categories of words. From the perspective of word class distribution patterns, we suppose that the birth of modern Chinese poetry in the 1910s is a sharp change to Chinese poetry production.